The first integral method for the perturbed Wadati-Segur-Ablowitz equation with time dependent coefficient - İnç, Mustafa; Kilic, Bulent (Academic Publication Council, 2016)
The first integral method (FIM) is used to construct traveling wave solutions of perturbed Wadati-Segur-Ablowitz (pWSA) equation with time dependent coefficient in this manuscript. We obtained some different solutions by using Gauge transformation with time dependent coefficient of variable transformations. The method is an effective method to construct the different types of exact solutions of nonlinear partial differential equations (NPDE).
Keywords: Analytical solutions; FIM; pWSA; traveling wave solutions